2010
DOI: 10.1351/pac-con-09-12-09
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoramidite-rhodium complexes as catalysts for the asymmetric [2 + 2 + 2] cycloaddition of alkenyl isocyanates and alkynes

Abstract: The discovery and development of the asymmetric rhodium-catalyzed [2+2+2] cycloaddition of alkenyl isocyanates and exogenous alkynes to form indolizinone and quinolizinone scaffolds is described. This methodology has been expanded to include substituted alkenes and dienes, a variety of sterically and electronically diverse alkynes, and carbodiimides in place of the isocyanate. Through X-ray analysis of Rh(cod)/phosphoramidite complexes, additives that modify the enantio-determining step, and other experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Enantioselective rhodium-catalyzed [2 + 2+2]/[4 + 2+2] cycloadditions of isocyanates/carbodiimides bearing terminal alkenes/1,3-dienes with aromatic terminal alkynes, aliphatic terminal alkynes, , or internal alkynes (Figure ) were first developed by Rovis and co-worker with chiral TADDOL/biphenol-derived monophosphoramidite ligands, which was well-reviewed in 2009. Mechanistic studies indicated that the elimination/reinsertion of CO was involved in the cycloaddition.…”
Section: Asymmetric Coupling Of π-Systemsmentioning
confidence: 99%
“…Enantioselective rhodium-catalyzed [2 + 2+2]/[4 + 2+2] cycloadditions of isocyanates/carbodiimides bearing terminal alkenes/1,3-dienes with aromatic terminal alkynes, aliphatic terminal alkynes, , or internal alkynes (Figure ) were first developed by Rovis and co-worker with chiral TADDOL/biphenol-derived monophosphoramidite ligands, which was well-reviewed in 2009. Mechanistic studies indicated that the elimination/reinsertion of CO was involved in the cycloaddition.…”
Section: Asymmetric Coupling Of π-Systemsmentioning
confidence: 99%
“…1 reports the most known indolizidine 167B bearing a propyl chain on the C5 position), act as noncompetitive nicotinic inhibitors, suggesting their potential efficiency for the design of drugs for the central nervous system. 3,4 Because of their scarcity in natural sources, the chemical synthesis of these alkaloids have benefited from a worldwide interest, and a large number of racemic [5][6][7][8][9] and enantiomeric [10][11][12][13][14][15][16][17][18][19] strategies have been reported to provide these natural compounds.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In 2011, we reported an asymmetric [4 + 2] cycloaddition of α,β-unsaturated imines and isocyanates catalyzed by a rhodium(I)/ phosphoramidite ( L1 ) complex. 9e This reaction allows facile access to pyrimidinones in good yields and high enantioselectivities.…”
mentioning
confidence: 99%
“…Our group has been interested in the development of rhodium-catalyzed asymmetric syntheses of nitrogen-containing heterocycles. , In 2011, we reported an asymmetric [4 + 2] cycloaddition of α,β-unsaturated imines and isocyanates catalyzed by a rhodium­(I)/phosphoramidite ( L1 ) complex . This reaction allows facile access to pyrimidinones in good yields and high enantioselectivities.…”
mentioning
confidence: 99%